Citation Context Classification: Critical vs Non-critical - Te, Sonita; Barhoumi, A.; Lentschat, Martin; Bordignon, Frédérique; Labbé, Cyril; Portet, François (HAL (Le Centre pour la Communication Scientifique Directe), 2022)
International audience